Phytoremediation potential of coffee pod (Cassia tora): An in situ approach for attenuation of chromium from overburden soil of Sukinda Chromite Mine, India. Issue 2 (12th August 2020) - Patra, Deepak Kumar; Grahacharya, Aradhana; Pradhan, Chinmay; Patra, Hemanta Kumar
Abstract: Pot experiments were conducted for 60 days to investigate the phytoremediation potential of Cassia tora grown in different concentrations of chromium (Cr) rich overburden soil (OBS) of Sukinda Chromite Mine (10, 20, 30, 40, 50, 70, and 100%). To assess the phytoaccumulation ability of C. tora, the tolerance index (TI), bio‐concentration factor (BCF), transportation index (Ti), and total accumulation rate (TAR) were measured. The results showed that at 100% OBS the TI, BCF, Ti, and TAR of C. tora have 23.89, 0.28, 60.25, and 7.46, respectively. The Cr recovery from contaminated soil by C. tora was notable as reported to be 6.25, 11.6, 12.75, 14.2, 17.35, 22.65, and 17.7 mg/kg, respectively. The outcome indicated that C. tora is a potential phytoremediator of Cr from contaminated sites due to its high bioaccumulation activity, high tolerance, and Ti. Therefore, C. tora can be suggested for phytostabilization program to lessen toxic Cr from chromite overburden mining sites.